Hopes and Fears: Community Cohesion and the 'White Working Class' in One of the 'Failed Spaces' of Multiculturalism. (April 2018) - Thomas, Paul; Busher, Joel; Macklin, Graham; Rogerson, Michelle; Christmann, Kris
Since 2001, community cohesion has been an English policy concern, with accompanying media discourse portraying a supposed failure by Muslims to integrate. Latterly, academia has foregrounded White majority attitudes towards ethnic diversity, particularly those of the 'White working class'. While questioning this categorisation, we present data on attitudes towards diversity from low income, mainly White areas within Dewsbury, West Yorkshire, a town portrayed in media discourse as one of the 'failed spaces' of multiculturalism. Drawing on mixed methods research, we present and discuss data that provide a complex message, seemingly confirming pessimistic analyses around ethnic diversity and predominantly White neighbourhoods but also highlighting an appetite within the same communities for greater and more productive inter-ethnic contact. Furthermore, anxieties about diversity and integration have largely failed to coalesce into broad support for organised anti-minority politics manifest in groups such as the English Defence League.